Types of corn grown in Uzbekistan and their peculiarities - Pirimqulova Muhabbat Xayitovna; Mamarajabov Samandarbek Faxriddinovich (Zien Journals, 2022)
This article describes some species of corn of the cereal family, including varieties grown in Uzbekistan and their characteristics, ways to increase their productivity through intensive methods and their importance in agriculture
Keywords: Oats; Grain oats; broom oats; Chillaki